A kaleidoscope career perspective on faculty sabbaticals. Issue 3 (3rd June 2014) - M. Carraher, Shawn; M. Crocitto, Madeline; Sullivan, Sherry
Abstract : Purpose: – Although the sabbatical leave is an integral part of academic life, there has been relatively little empirical, theory-driven research of the process. The purpose of this paper is to integrate the limited research on faculty sabbaticals with the careers literature to offer a new approach for the study of this important tool for faculty development. Design/methodology/approach: – A review of the empirical studies on faculty sabbaticals was performed and used in conjunction with the kaleidoscope career model (KCM) and the theory of planned behavior (TPB) to develop a model to guide future research. Findings: – The decision to take a sabbatical is complex and may have long-lasting implications for an individual's career. It is important to examine how factors that impact the perceived feasibility of the sabbatical (e.g. organization, country social norms) and desirability (e.g. need for authenticity, balance and challenge) influence the decisions, goals and outcomes of the sabbatical. Research limitations/implications: – The use of the KCM, the TPB and the careers literature provides a theoretical foundation to study faculty sabbaticals as a distinct event in an individual's career development. Practical implications: – The proposed framework can be used by faculty members to determine the feasibility and desirability of taking a sabbatical as well as what factors which may encourage or limit sabbatical opportunities. Originality/value: – This conceptual paper uses a careers lens to provide a theory-driven framework which can be used to conduct much needed research on faculty sabbaticals.